Muscle strength in diabetics compared to non-diabetic elderly subjects: A cross sectional and case-control study - Mohammad Rahimi; Payam Saadat; Seyed reza Hosseini; Mohammadali Bayani; Ali Bijani (Babol University of Medical Sciences, 2019)
Background: With the growing population of the elderly, the prevalence of disabilities and chronic diseases will also likely increase. Muscle weakness leads to low amounts of physical activity in elderly diabetic patients and makes them susceptible to falls. In this study, we aimed to compare the muscle strength between diabetic and non-diabetic elderly individuals. Methods: The present study is part of the the Amirkola Health and Ageing Project (AHAP) cohort performed on 1320 elderly individuals. Diabetic and non-diabetic subjects were considered as case and control groups, respectively. A diagnosis of diabetes was assigned to patients who were previously diagnosed and those with repeated fasting blood sugar FBS≥126mg/dl. Digi Hand Dynamometer device and manual muscle testing (MMT) grading systems were used to assess muscle force in the upper and lower extremities, respectively. Data were then analyzed and p<0.05 was considered significant. Results: 29.8% of the total participants (n=393) were diabetics. In the case group, 143 (36.4% of all diabetics) had weak upper extremity muscles. The number was 314 (33.9%) among non-diabetics (P=0.38). We saw decreased lower extremity muscle force in 134 (34.1%) diabetic individuals and 292 (31.5%) non-diabetics (P=0.35). Statistical analysis showed no significant difference in any of the lower or upper extremity muscle forces between diabetics and non-diabetics (p>0.05). Conclusion: Our findings indicate that diabetes mellitus (DM) affects neither the upper nor the lower extremity muscle force in the elderly.